2013
DOI: 10.1088/0957-4484/24/11/115101
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle toxicity in the embryonic zebrafish is governed by particle dispersion and ionic environment

Abstract: The mechanism of action of silver nanoparticles (AgNPs) is unclear due to the particles’ strong tendency to agglomerate. Preventing agglomeration could offer precise control of the physicochemical properties that drive biological response to AgNPs. In an attempt to control agglomeration, we exposed zebrafish embryos to AgNPs of 20 or 110 nm core size, and polypyrrolidone (PVP) or citrate surface coatings in media of varying ionic strength. AgNPs remained unagglomerated in 62.5 μM CaCl2 (CaCl2) and ultrapure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 35 publications
(63 reference statements)
7
81
0
2
Order By: Relevance
“…28 To minimize agglomeration with salts present in zebrafish embryo medium, the ZnO NP exposures were conducted in ultrapure water. 28,29 As previously reported in Wehmas et al, this ZnO NP has a mean hydrodynamic diameter on the order of microns when prepared in zebrafish embryo medium, whereas its mean hydrodynamic diameter is *400 nm and zeta potential (an indication of charge) is *20.2 mV when prepared in ultrapure water creating a more stable exposure suspension. 28 Following addition of compound, the 96-well plates were sealed with Parafilm, wrapped in aluminum foil to block incidental light and maintained in a 33°C -1°C incubator until 7 DPF.…”
Section: Zinc Oxide Nanoparticlesupporting
confidence: 62%
“…28 To minimize agglomeration with salts present in zebrafish embryo medium, the ZnO NP exposures were conducted in ultrapure water. 28,29 As previously reported in Wehmas et al, this ZnO NP has a mean hydrodynamic diameter on the order of microns when prepared in zebrafish embryo medium, whereas its mean hydrodynamic diameter is *400 nm and zeta potential (an indication of charge) is *20.2 mV when prepared in ultrapure water creating a more stable exposure suspension. 28 Following addition of compound, the 96-well plates were sealed with Parafilm, wrapped in aluminum foil to block incidental light and maintained in a 33°C -1°C incubator until 7 DPF.…”
Section: Zinc Oxide Nanoparticlesupporting
confidence: 62%
“…Different types of superficial agents may generate coating-specific behavior of AgNPs in solution [66] or in physiological fluids [13], and consequently may cause different antimicrobial or toxic effects.…”
Section: Toxicity Of Agnpsmentioning
confidence: 99%
“…Among other effects, it was demonstrated that carbon-coated silver nanoparticles influence cell viability to a lesser extent than uncoated AgNPs of similar size [95], whereas polysaccharide-coated AgNPs cause more severe effects than uncoated AgNPs [1]. Moreover, it was shown that PVP-coated [66] or peptide-coated [51] AgNPs are more toxic than citrate-coated AgNPs with similar particle core sizes.…”
Section: Toxicity Of Agnpsmentioning
confidence: 99%
“…Silver is one of the most prominent non-small-molecule drugs used for antibacterial applications, 3,[17][18][19] but can be expensive and mildly toxic to surrounding mammalian cells. 20,21 Additionally, adding different materials to the surface may lead to imperfectly fused layers that may eventually wear or delaminate from the bulk implant.…”
Section: Introductionmentioning
confidence: 99%